Totemisme dan Pergeserannya: Studi Terhadap Tradisi Lokal di Sendang Mandong, Klaten, Jawa Tengah - Muh. Syamsuddin (UIN Sunan Kalijaga Yogyakarta, 2017)
Totemism that Emile Durkheim calls the origin of belief in the sacred, is also found in Sendang Mandong, Klaten, Central Java. Bulus as a totem is a representation of a local mythological figure, Kyai Gringsing. Reverence for this mythological figure not only helps the conservation of the environment, especially water resources, but also breeds a tradition that run for decades. The tradition includes the merit sendang wayangan, mangan bulus for the bride, and offerings. The tradition is also a form of ecounter between totemism with the influence of Islam. As the result, Islam Kejawen is existing in Mandong Village. However, the Islam Kejawen is local narrative of totemism and then Islam Kejawen is undocumented and not inherited either in writing or oral tradition. The local narrative is futher undermind by the changes caused by education, modernity, and the development of puritan religious stream.